Exploring logical and hierarchical information to map relational databases into ontologies. (18th May 2019) - Tissot, Hegler; Huve, Cristiane Aparecida Gonçalves; Peres, Leticia Mara; Fabro, Marcos Didonet Del
Ontologies are formal specifications of conceptualisations. Their designs require to understand the concepts involved in the domain to be mapped. One well-known method to produce ontologies is to extract their concepts from relational databases. We conducted a practical study over a real-world scenario on applying existing rules and we identified open issues to be addressed, such as the utilisation of logical metadata as a proper vocabulary, the implementation targeted to specific domains and mappings of hierarchical and self-hierarchical structures. In this paper, we present a novel approach that overcomes these issues. Our solution uses physical and logical models to enrich the terminology produced in the target ontology. It also contains a more comprehensive set of rules, taking into account instances and (self) hierarchies. We validate our approach with two experiments from the healthcare domain as input.